Predictors of preventive behaviors of AIDS/HIV based on Health Belief Model constructs in women with high-risk sexual behaviors: A cross-sectional survey - Mehri Alizade; Azizeh Farshbaf-Khalili; Jamileh Malakouti; Mojgan Mirghafourvand (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Worldwide, AIDS is an acute problem. Health Belief Model (HBM) is a model for prevention and control of diseases. This study examined the predictors of preventive behaviors of HIV/AIDS based on HBM constructs in participants. MATERIALS AND METHODS: This cross-sectional study was performed on 200 women who were referred to vulnerable women's centers across Tabriz city between November and December 2018. Participants were selected by census sampling. Inclusion criteria were having a health record, multiple sexual partners, reading and writing skills, and willingness to participate in the study. To collect data, questionnaires of sociodemographic characteristics, HIV knowledge, self-efficacy for negotiating safe sex, perceived sensitivity, perceived severity, perceived benefits, perceived barriers, and behavioral prevention (BP) were used. The collected data were analyzed using SPSS version 19 through Pearson's correlation coefficient, one-way ANOVA, and multiple linear regression analyses. The significant level was set at α = 0.05. RESULTS: Pearson's correlation test showed a statistically significant correlation between BP and perceived sensitivity (r = 0.25), perceived benefits (r = 0.32), self-efficacy (r = 0.33), and HIV knowledge (r = 0.25) constructs (P < 0.001). According to the multiple linear regression, perceived sensitivity (P = 0.020), perceived benefits (P = 0.036), and some of the sociodemographic characteristics were found to be predictors of preventive behaviors that explained in total 50% of variance of BP (P < 0.05 and R2 = 0.504). CONCLUSION: It seems that the HBM is useful to predict HIV preventive behaviors among this vulnerable group. Training programs should be aimed on improving the health belief of HIV preventive behaviors.